Analysis Of The Preparation Of Risk-Based Annual Supervision Work Program (Pkpt) At The Banyuwangi Regency Inspectorate - Drajad Surya Maulana; Siti Maria Wardayanti; Alwan Sri Kustono; Wasito Wasito (Journal of Social Research, 2024)
This research aims to provide information and reference materials related to the Annual Supervision Work Program (PKPT) for the Banyuwangi Regency Inspectorate agency. This research is qualitative. The results of this research are expected to improve the Banyuwangi Regency Inspectorate to improve its work program based on risk. Risk-based PKPT guidelines were also made by researchers so that they could be the basis for making risk-based PKPT. The method used in this study is qualitative. The result of this study is the formation of a risk-based PKPT in accordance with regional development goals. The risk-based concept has begun to be mitigated from the beginning so that the assignments that will be carried out by auditors are going well. The existence of inhibiting factors in the preparation of risk-based PKPT can be minimized by auditors so that the goals of the Inspectorate organization can be achieved.